Utilisation of systemic therapy options in routine treatment of metastatic colorectal cancer in Australia. Issue 2 (9th February 2020) - Delahunty, Rachel; Lee, Margaret; Wong, Hui‐Li; Johns, Julie; Mckendrick, Joseph; Lee, Belinda; Kosmider, Suzanne; Cooray, Prasad; Ananda, Sumitra; Desai, Jayesh; Tran, Ben; Tie, Jeanne; et al.
Abstract: Background: In the treatment of metastatic colorectal cancer (mCRC), exposure to all three active cytotoxic agents, 5‐fluorouracil/capecitabine, irinotecan and oxaliplatin, improves overall survival. The addition of biologic agents (bevacizumab and cetuximab/panitumumab) further improves survival. The uptake of available systemic agents for mCRC in routine practice in Australia is poorly described. Methods: The ACCORD database was interrogated to determine demographics, treatments and outcomes for patients diagnosed with mCRC between 1 January 2011 and 1 January 2016 at six Melbourne centres. Results: About 1130 mCRC patients were identified: median age was 69 years (range 26–105); 61% had synchronous disease. KRAS status was known in 62%, of whom 49% were KRAS wild‐type. At the time of analysis, 67% of all patients had commenced systemic treatment, 50% had received two or more lines of therapy and 19% of KRAS wild‐type patients had received all five active drugs. Of KRAS‐ mutated patients, 35% had received all four Pharmaceutical Benefits Scheme–reimbursed active drugs. Patients who had not received chemotherapy included 72 patients who underwent metastasectomy alone. At a median follow up of 34 months, median overall survival was 25 months for all patients and 69 months for those who underwent metastasectomy. Conclusion: In this community‐based cohort, 33% of patients had not received any systemic therapy for mCRC, and few patients had received all available active systemic agents. As many patients remain alive, these figures will likely increase over time. The overall survival of patients with mCRC in this community‐based cohort was 25 months and not dissimilar to that achieved in recent clinical trials.